Effect of Season on Performance of Broiler Chicken under Deep Litter System of Management in Assam - Sarma, M.; Borah, M. K.; Kalita, K. P.; Mahanta, J. D.; Kalita, N.; Talukdar, J. K.; Deka, P.; Amonge, T. K.; Islam, R. (International Journal of Livestock Research, 2019)
A total of 30 broiler farms (6 farms in each of 5 selected agro-climatic zones) were selected randomly to study the effect of season on the performance of broiler chicken in Assam. For this purpose, 400 Cobb commercial broiler chicks were utilized and were fed with ad-libitum commercial broiler feed under standard managemental conditions. The final body weight was highest during winter season (2719.95±5.92g) followed by pre-monsoon and post-monsoon season and was significantly low in monsoon season. Best FCR was found during post-monsoon (1.61) followed by pre-monsoon (1.63) as compared to winter (1.74) and monsoon season (1.76). The feed consumption and live body weight were also higher in winter season. Livability percentage varied with age and season. The BCR was recorded highest during winter season (1.20). Therefore, the best season for the small-scale broiler farmers to earn profitability in all the selected agro climatic zones was winter though they need to take extra care during chick period.